The heterozygous mutation COL4A4 c.817-1G>A causes Alport syndrome in a Chinese family: a case report - Wang, Dayan; Li, Xiaobing; Cheng, Kaichao; Zheng, Lanjin; Yu, Pengfei; Lai, Panjian (Frontiers in Pediatrics, 2025)
BackgroundAlport syndrome is an inherited glomerular disease that leads to progressive kidney failure, hearing loss, and eye problems. Diagnosis mostly relies on tests of tissue pathology and genetic analysis. This study aims to clarify the role of the COL4A4 c.817-1G > A mutation in Alport syndrome. The COL4A4 gene encodes the α4 chain of type IV collagen, which is a key component of the glomerular basement membrane. Mutations in this gene are strongly linked to Alport syndrome.MethodsWe collected clinical data from a 12-year-old boy who had “persistent hematuria for 4 years” and performed a renal biopsy, which was pathologically diagnosed as “Alport syndrome”. We used high-throughput sequencing technology to conduct whole-exome sequencing (WES) and Sanger sequencing for the patient and his parents. Through bioinformatics analysis, we found that the COL4A4 c.817-1G > A mutation may lead to splicing abnormalities. We extracted RNA from the patients blood and urine samples and used in vivo splicing validation to study the impact of the mutation on mRNA.ResultsOur findings show that the COL4A4 c.817-1G > A mutation disrupts mRNA splicing. This mutation affects the splice acceptor site of Intron 13, which is next to Exon 14, causing a 1-bp deletion before Exon 14 and creating a premature stop codon. Consequently, a truncated protein of 273 amino acids is produced, as opposed to the full-length protein of 1,690 amino acids. This finding clarifies the molecular mechanism by which this mutation contributes to Alport syndrome.ConclusionOur study finds that the COL4A4 c.817-1G > A variant may cause autosomal dominant Alport syndrome. Our research expands the mutation spectrum of Alport syndrome while aiding in genetic counseling and diagnosis for affected patients.